Environmental ethics constructive approaches to difficult issues - Group Four Teleproductions (Durango, Colorado : Group Four Teleproductions, 1994)
Provides educators with a model for discussing environmental issues. Using common land use conflicts, it explores biological and economic impacts as well as the emotional factors that influence people's perspectives and beliefs. Helps students to understand how different ethics are formed and challenges them to observe the origins of their own belief systems
Title from title screen
DVD format
Keywords: Environmental ethics -- United States; Environmental education -- United States